2017
DOI: 10.1371/journal.pone.0176106
|View full text |Cite
|
Sign up to set email alerts
|

15-hydroxyprostaglandin dehydrogenase (15-PGDH) prevents lipopolysaccharide (LPS)-induced acute liver injury

Abstract: The NAD+-dependent 15-hydroxyprostaglandin dehydrogenase (15-PGDH) catalyzes the oxidation of the 15(S)-hydroxyl group of prostaglandin E2 (PGE2), converting the pro-inflammatory PGE2 to the anti-inflammatory 15-keto-PGE2 (an endogenous ligand for peroxisome proliferator-activated receptor-gamma [PPAR-γ]). To evaluate the significance of 15-PGDH/15-keto-PGE2 cascade in liver inflammation and tissue injury, we generated transgenic mice with targeted expression of 15-PGDH in the liver (15-PGDH Tg) and the animal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(24 citation statements)
references
References 27 publications
4
20
0
Order By: Relevance
“…Earlier studies have demonstrated LPS‐induced acute liver injury . Here, we found that LPS caused a significant decrease in liver weight, hepatic glycogen and TG content but an increase in liver protein content (Fig.…”
Section: Resultssupporting
confidence: 59%
See 1 more Smart Citation
“…Earlier studies have demonstrated LPS‐induced acute liver injury . Here, we found that LPS caused a significant decrease in liver weight, hepatic glycogen and TG content but an increase in liver protein content (Fig.…”
Section: Resultssupporting
confidence: 59%
“…1E-J). Collectively, these results demonstrated LPS induced body weight losses, blood glucose decrease, insulin The effect of insulin on LPS-induced liver injury and activation of hepatic NF-jB pathway Earlier studies have demonstrated LPS-induced acute liver injury [20,21]. Here, we found that LPS caused a significant decrease in liver weight, hepatic glycogen and TG content but an increase in liver protein content ( Fig.…”
Section: Peripheral Insulin Alleviated Systemic Metabolic Disorders Isupporting
confidence: 69%
“…Although their functions are not well characterised, several studies report physiological effects. For example, 15-keto-PGE 2 can inhibit inflammatory cytokine production in acute liver injury (62) and 15-PGDH activity suppresses colon tumorigenesis in vivo (63) . How dietary n-3 PUFA affects PGDH activity or whether its oxylipins play functional roles in the heart by increasing these PG metabolites remains to be elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, we found that PPAR-γ receptor antagonist administration resulted in an increased hepatocyte injury, apoptosis, and the pro-inflammatory NO+ Kupffer cell population when compared to the untreated control group. It is possible that the increased injury with PPAR-γ receptor antagonist administration results from the additional blockage of endogenous PPAR-γ activation [ 52 ]. This suggests that the PPAR‒γ pathway could have an important internal protective auto-regulatory mechanism to diminish the exaggerated inflammatory response following IRI.…”
Section: Discussionmentioning
confidence: 99%